Factors associated with epiphora following orbital‐sparing maxillectomy via modified Weber–Ferguson incision with lower blepharoplasty. Issue 5 (1st February 2021) - Pitak‐Arnnop, Poramate; Subbalekha, Keskanya; Meningaud, Jean‐Paul; Sirintawat, Nattapong; Auychai, Prim; Tangmanee, Chatpong; Wunsch, Annette; Neff, Andreas
Abstract: Purpose: The aims of the study were to estimate the frequency of epiphora and to identify factors associated with epiphora after orbital‐sparing maxillectomy via modified Weber–Ferguson incision with lower blepharoplasty (OSOSM‐MWFILB). Methods: We performed a retrospective cohort study enrolling a sample derived from the patient population undergoing OSM‐MWFILB over a 7‐year period. The predictor variables were grouped into demographic, related health status, anatomic, tumor‐specific, and therapeutic categories. The primary outcome variable was the presence of postmaxillectomy epiphora (PME). Descriptive, univariate, and multivariate regression mixed‐effect models were computed. Results: The study sample was composed of 134 patients (46.3% females; 71.6% squamous cell carcinomas) with a mean age of 64.7 ± 12.2 years. There were 23 (17.2%) PME events, which were significantly associated with eight variables: male gender, poor general health (ASA III–IV), large vertical defect (Brown and Shaw's class III–IV), squamous cell carcinoma tumor type, big tumor size (T3‐4), cervical lymph node metastasis (N1‐2), long operating time > 3 h, and adjuvant radio(chemo)therapy in both univariate mixed regression and multivariate Cox hazards analyses. Healing of PME in irradiated patients was significantly delayed. Conclusions: Ophthalmologic consequences in patients undergoing OSM‐MWFILB require particular attention, especially in case of advanced tumors, multiple comorbidities, or long surgery with postoperative radio(chemo)therapy. This emphasizes the importance of appropriate cooperation between the surgeons and ophthalmic colleagues.